Apoptosis and Antiproliferation of Tespong Herbs (Oenanthe javanica (Blume) DC) Fraction Against MCF 7 Breast Cancer Cell - Agustina Putri; Haryoto; Indrayudha Peni (BIO Web of Conferences)
Breast cancer is now commonly treated with chemotherapy. The main problem in breast cancer treatment is the emergence of resistance and low efficacy of drugs. With so many side effects, it encourages many researchers to look for alternative breast cancer treatments. One possibility is the use of plant-derived natural anticancer agents, namely Herba Tespong (Oenanthe javanica (Blume) DC). Oenanthe javanica contains coumarins, flavonoids, flavonoid glycosides and polyphenols. The aim of this study was to examine the cytotoxicity, antiproliferative and apoptotic effects of a fraction active of the herb tespong (Oenanthe javanica (Blume) DC) on MCF7 cells. The antiproliferation test method used is MTT by examining doubling time values and apoptosis using double staining method. From the results of the study, the IC50 value of the active fraction of tespong herb was 41,35 μg/mL and was categorized as moderately active. The results obtained show that the active isolate was able inhibit the proliferation of MCF7 cells at IC50 concentration of 41,35 μg/ml with a doubling time of 32,32 hours. Apoptosis assays showed cell death at an IC50 concentration of 41,35 µg/mL.